2022
DOI: 10.1007/s12144-022-03784-7
|View full text |Cite
|
Sign up to set email alerts
|

How parents assist children’s emotion regulation in Turkey: The Turkish adaptation of the parental assistance with child emotion regulation (PACER) questionnaire

Abstract: Parents play a critical role in emotional socialization and the development of emotion regulation during childhood. The tools to measure how parents assist children's emotion regulation are very limited. The Parental Assistance with Child Emotion Regulation (PACER) Questionnaire is a novel scale developed for this purpose with excellent psychometric properties. The aim of this study is to adapt the PACER to Turkish and investigate its psychometric properties in the Turkish cultural setting. The data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…An interesting finding of the correlational analysis suggested that parenting style significantly affects the choice of emotion regulation strategy chosen by children. A higher score on the scale of parenting style was negatively related to the use of maladaptive emotion regulation strategies ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding of the correlational analysis suggested that parenting style significantly affects the choice of emotion regulation strategy chosen by children. A higher score on the scale of parenting style was negatively related to the use of maladaptive emotion regulation strategies ( 62 ).…”
Section: Discussionmentioning
confidence: 99%